THE EFFECT OF VIRTUAL LEARNING THROUGH ONLINE LEARNING SYSTEM (SPADA) ON STUDENTS' LEARNING OUTCOMES IN ALGEBRAIC STRUCTURE COURSE IN DEPARTMENT OF MATHEMATICS EDUCATION, MUHAMMADIYAH UNIVERSITY OF MAKASSAR - St. Nur Humairah Halim; Sitti Rahmah Tahir; Randy Saputra Mahmud; Ilham Syata; Dwi Novitasari (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine the effect of treatment on student learning outcomes in the algebraic structure course at the Department of Mathematics Education of the University of Muhammadiyah Makassar in virtual learning through the online learning system (SPADA). This study is a quasi-experimental design with a post-test-only control group whose results were analyzed using descriptive analysis and inferential analysis (mann whitney test). The population is the class of 2019 who is programming an algebraic structure course consisting of 3 classes, then a sample consisting of 2 classes was selected, namely, one experimental class taught through SPADA, and one control class taught in addition to using SPADA, namely, zoom meeting, google meet, email, and whatsApp groups. The instrument used is a test of student learning outcomes. The results obtained are that the average learning outcomes of students who are taught through SPADA are higher than the average learning outcomes of students who are taught other than through SPADA, but the results of the Mann Whitney test show that there is no significant difference from the learning outcomes of students who have been taught through SPADA or other than SPADA. Researchers suggest that providing virtual learning not only relies on one learning media but also on the synergy between one media and another, which will further optimize virtual learning.